Lithium ion secondary battery

By using silicon-carbon materials with specific structures and sulfur-containing heterocyclic compounds in lithium-ion batteries, combined with the adjustment of electrolyte, the deformation and cracking of silicon-based materials in lithium-ion batteries is solved due to volume changes, and the battery is improved Kinetics and thermal safety performance.

CN119324255APending Publication Date: 2025-01-17ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411352777.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing silicon-based materials are deformed and cracked due to volume changes in lithium-ion batteries, increasing side reactions, affecting the dynamic performance and safety of the battery.

Method used

Add carboxylic acid ester solvent and sulfur-containing heterocyclic compounds to the electrolyte, and use silicon carbon materials with specific structures in the negative electrode sheet to adjust its spherical shape and the mass proportion of the compounds in the electrolyte to take into account the kinetic properties and cycles Stability and thermal safety performance.

Benefits of technology

By adjusting the spherical shape of silicon-carbon materials and the electrolyte composition, the good kinetic performance, high cycle stability and thermal safety performance of lithium-ion batteries are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324255A_ABST
    Figure CN119324255A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a lithium ion secondary battery. The battery comprises a positive plate, a negative plate and electrolyte, the negative plate comprises a negative active material, and the negative active material comprises a carbon-based material and a silicon-based material; the silicon-based material comprises a silicon carbon material; the silicon-carbon material comprises a porous carbon substrate and a silicon material distributed in pores of the porous carbon substrate; the sphericity degree of the silicon carbon material is recorded as Q, and the sphericity degree Q is 0.5-1; the electrolyte comprises a carboxylic ester solvent and a sulfur-containing heterocyclic compound; based on the total mass of the electrolyte, the mass ratios of the carboxylic ester solvent and the sulfur-containing heterocyclic compound are respectively recorded as E% and S%; e and S meet the condition that E / S is more than or equal to 10 and less than or equal to 100, so that the lithium ion battery has good dynamic performance, relatively high energy density, relatively good cycling stability and relatively good thermal safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] In recent years, with the popularity of electric vehicles and portable devices, the requirements for lithium battery performance have become increasingly higher. Silicon-based materials have a higher theoretical capacity and can store more lithium ions at the same volume and weight compared to traditional graphite negative electrodes, greatly improving the energy density of the battery. However, existing silicon-based materials are prone to significant volume changes during the charging and discharging process, resulting in deformation and cracking of the silicon-carbon negative electrode, which continuously increases the direct contact between the silicon-based material and the electrolyte, causing more side reactions, causing serious gas and heat generation in the battery, and prone to battery fires and other safety issues; at the same time, the increase in side reactions further leads to the thickening of the SEI film, resulting in an increase in the internal resistance of the battery, which hinders the transmission of lithium ions. In addition, the cracking of the pole piece causes the original continuous electron and ion transmission path to be interrupted, which also hinders the transmission of lithium ions, thereby affecting the kinetic performance of the battery. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide a lithium ion secondary battery, wherein a carboxylate solvent and a sulfur-containing heterocyclic compound are added to an electrolyte, and at the same time, a silicon-carbon material with a specific structure is added to a negative electrode sheet, and by further adjusting the relationship between the sphericity of the silicon-carbon material and the mass proportion of the sulfur-containing heterocyclic compound in the electrolyte, and the relationship between the mass proportion of the carboxylate solvent and the sulfur-containing heterocyclic compound in the electrolyte, the lithium ion battery can have good kinetic performance, good cycle stability and good thermal safety performance.

[0004] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the sphericity Q of the silicon-carbon material is 0.5-1;

[0006] The electrolyte includes a carboxylate solvent; based on the total mass of the electrolyte, the mass proportion of the carboxylate solvent is recorded as E%;

[0007] The electrolyte includes a sulfur-containing heterocyclic compound; the mass proportion of the sulfur-containing heterocyclic compound is recorded as S% based on the total mass of the electrolyte;

[0008] E and S satisfy: 10≤E / S≤100.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] The lithium ion secondary battery provided by the present invention adds a carboxylate solvent and a sulfur-containing heterocyclic compound to the electrolyte, and uses a silicon-carbon material with a specific structure at the negative electrode. The silicon-carbon material includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate. By further adjusting the sphericity Q of the silicon-carbon material within the range of 0.5-1, and adjusting the mass proportion E of the carboxylate solvent and the mass proportion S of the sulfur-containing heterocyclic compound in the electrolyte to satisfy 10≤E / S≤100, the lithium ion battery can have good kinetic performance, good cycle stability and good thermal safety performance.

[0011] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 FIG. 1 is a schematic diagram showing a structure of a negative electrode active material layer in an embodiment of the present invention.

[0013] Figure 2 FIG. 2 is another schematic diagram of the structure of the negative electrode active material layer in an embodiment of the present invention.

[0014] Figure 3 Shown is a cross-sectional schematic diagram of the silicon-carbon material in an embodiment of the present invention.

[0015] Figure numerals: 1, depressed area; 2, pit; 3, negative electrode active material layer; 4, silicon material; 5, porous carbon skeleton; 6, carbon coating layer. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0018] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0019] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0020] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the sphericity Q of the silicon-carbon material is 0.5-1;

[0021] The electrolyte includes a carboxylate solvent; based on the total mass of the electrolyte, the mass proportion of the carboxylate solvent is recorded as E%;

[0022] The electrolyte includes a sulfur-containing heterocyclic compound; the mass proportion of the sulfur-containing heterocyclic compound is recorded as S% based on the total mass of the electrolyte;

[0023] E and S satisfy: 10≤E / S≤100.

[0024] Exemplarily, the sphericity Q can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any point value in the range consisting of any two of the above point values.

[0025] Exemplarily, the value of E / S may be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or any point value in the range consisting of any two of the above point values.

[0026] In some embodiments, Figure 3 As shown, the silicon-carbon material includes a core and a carbon coating layer 6 coated on the core, and the core includes a porous carbon substrate 5 and silicon material 4 distributed in the pores of the porous carbon substrate.

[0027] The present invention adds a silicon-carbon material with a specific structure to the negative electrode sheet. The porous carbon substrate structure in the core of the silicon-carbon material is not only conducive to the deposition of silicon materials, but also its good conductivity can reduce the polarization of silicon materials in lithium insertion and extraction. The pores (gaps or pores) in the porous carbon substrate can also limit the size of the silicon material in the pores, so that the size of the silicon material is not too large, so that the structure of the silicon-carbon material is more suitable for the rapid insertion and extraction of lithium ions, and improve the dynamic performance of the battery. However, although the silicon-carbon material can improve the dynamic performance of the battery to a certain extent, the thermal safety problem caused by the volume expansion of the silicon-containing negative electrode still exists. The present invention adds sulfur-containing heterocyclic compounds to the electrolyte. On the one hand, the sulfur-containing heterocyclic compounds can form a film on the surface of the positive electrode to inhibit the dissolution of positive metal ions; on the other hand, the sulfur-containing heterocyclic compounds can also form a film on the surface of the negative electrode, which is conducive to inhibiting the volume expansion of the silicon-containing negative electrode; it can not only improve the cycle stability of the silicon-carbon material, but also inhibit the high-temperature gas production of lithium-ion batteries, thereby improving the thermal safety performance and cycle life of lithium-ion batteries.

[0028] Sulfur-containing heterocyclic compounds act on the surface of the negative electrode, and silicon-carbon particles will affect the overall appearance of the SEI film formed on the negative electrode. If the sphericity of the silicon-carbon material is too low, the silicon-carbon particles will expand / contract during battery charging / discharging, resulting in stress and strain concentration in the local area of ​​the negative electrode, and the SEI film is prone to repeated cracking and generation at this location, and the thickness of the formed SEI film is not uniform, and the consumption of the electrolyte is aggravated. Further research of the present invention has found that when the sphericity (Q) of the silicon-carbon material is in the range of 0.5-1, the silicon-carbon particles are smoother, which can make the sulfur-containing heterocyclic compounds more evenly distributed in the silicon-carbon particle area and the negative electrode surface, and the thickness of the formed SEI film is also more uniform, which improves the effect of inhibiting the expansion of the silicon-containing negative electrode and the high-temperature gas production of the battery, and further improves the thermal safety performance and cycle life of the lithium-ion battery.

[0029] Sulfur-containing heterocyclic compounds in the electrolyte will increase the battery impedance and reduce the battery's dynamic performance. In the present invention, by using linear carboxylates in combination with sulfur-containing heterocyclic compounds, adjusting the mass proportion of carboxylates solvent (E) and the mass proportion of sulfur-containing heterocyclic compounds (S) to meet 10≤E / S≤100, the decrease in dynamic performance caused by the increase in electrolyte viscosity brought about by the addition of sulfur-containing heterocyclic compounds to the electrolyte can be compensated; on the other hand, the use of linear carboxylates in combination with sulfur-containing heterocyclic compounds can also improve the fluidity of sulfur-containing heterocyclic compounds and further improve their film-forming uniformity.

[0030] In the present invention, by adjusting the sphericity Q within the range of 0.5-1, it is also possible to avoid the problem that when the sphericity of the silicon-carbon material is too low, the stress and strain in the local area are too concentrated, and the solid electrolyte membrane is prone to repeated cracking and generation in the area, resulting in excessive consumption of the electrolyte. It is also possible to avoid the large difference in lithium ion migration speed in different areas of the material surface caused by the uneven solid electrolyte membrane, which further aggravates the problem of uneven stress and strain.

[0031] Exemplarily, the testing method for sphericity Q may include the following steps: analyzing the image of each particle in the SEM photograph of the composite material at a certain magnification (for example, 2500 times) through image processing software (such as Image ProPlus) to obtain the circumference and area of ​​each particle, and respectively calculating the circumference equivalent radius r1 and area equivalent radius r2 of each particle, then the sphericity S of each particle = r2 / r1, and then performing quantitative weighted averaging of the sphericity of each particle to obtain the average sphericity of the silicon-carbon material composite material.

[0032] In summary, the present invention adopts a silicon-carbon material with a specific structure in the negative electrode sheet, adjusts the sphericity Q within the range of 0.5-1, and when E and S satisfy 10≤E / S≤100, the lithium-ion battery can have good kinetic performance, better cycle stability and better thermal safety performance.

[0033] In some embodiments, the mass proportion E of the carboxylate solvent is 30%-60%. The mass proportion E of the carboxylate solvent can be, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any point value in the range composed of the above two point values. When E further meets the above range, the viscosity of the electrolyte can be further reduced, and the conductivity of the electrolyte can be improved, thereby obtaining better dynamic performance. The mass proportion E of the carboxylate solvent meets the range of 30%-60%, which can avoid the situation that the improved dynamic performance effect is not obvious when E<30%, and avoid the degradation of the high temperature performance of the battery when E>60%.

[0034] In some embodiments, the mass proportion S of the sulfur-containing heterocyclic compound is 0.5%-5%, and the mass proportion S of the sulfur-containing heterocyclic compound can be, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any point value in the range of the above two point values. When S further meets the above range, it can avoid that when S<0.5%, the solid electrolyte film formed by the sulfur-containing heterocyclic compound on the surface of the positive and negative electrode materials is too thin and uneven, which has the disadvantage of limited improvement of the cycle and thermal stability of the lithium-ion battery; it can also avoid that when S>5%, the solid electrolyte film formed by the sulfur-containing heterocyclic compound on the surface of the positive and negative electrodes is too thick, resulting in excessive impedance of the lithium-ion battery, thereby deteriorating the charging window and cycle life of the lithium-ion battery. The mass proportion S of the sulfur-containing heterocyclic compound further meets the range of 0.5%-5%, further inhibits the occurrence of side reactions on the surface of the positive and negative electrode materials, improves the cycle stability of the silicon-carbon material, inhibits the high-temperature gas production of the battery, and further improves the cycle life and thermal safety performance of the battery.

[0035] In some embodiments, the sulfur-containing heterocyclic compound includes a sulfur-containing polyheterocyclic compound A, and / or a sulfur-containing monoheterocyclic compound B. Exemplarily, the sulfur-containing heterocyclic compound may be a sulfur-containing polyheterocyclic compound A, may be a sulfur-containing monoheterocyclic compound B, or may be a combination of a sulfur-containing polyheterocyclic compound A and a sulfur-containing monoheterocyclic compound B. Here, "polyheterocyclic" refers only to a compound having two or more heterocyclic rings, "monoheterocyclic" refers only to a compound having only one heterocyclic ring, and "heterocyclic" refers to a cyclic group containing different atoms, for example, a cyclic group containing S and C at the same time, or containing S, C and O at the same time, or containing S, C, O and N at the same time, etc.

[0036] To further improve the cycle life and thermal safety performance of the battery, in some embodiments, the sulfur-containing heterocyclic compound includes: a sulfur-containing polyheterocyclic compound A and a sulfur-containing monoheterocyclic compound B. Although the sulfur-containing polyheterocyclic compound A has a relatively large viscosity and a large impedance after film formation at the positive and negative electrodes, it is easier to form similar macromolecular cross-linked products due to its larger molecular weight, more functional groups, and more reaction sites. It can form a more stable solid electrolyte film on the surface of the positive and negative electrodes, thereby enabling the lithium-ion battery to have a better cycle life and improve the battery stability under extreme thermal conditions. The sulfur-containing monoheterocyclic compound B has a relatively smaller molecular weight, and its film formation stability at the positive and negative electrodes is slightly worse than that of the sulfur-containing polyheterocyclic compound A, but the solubility of the sulfur-containing monoheterocyclic compound B is relatively higher, and under normal conditions, it is easier to exist more stably in the electrolyte. During the thermal storage process, the sulfur monoheterocyclic compound B can continue to react and form a film on the surface of the positive and negative electrodes, inhibiting the reaction rate of other side reactions, so that the thermal storage gas production rate of the lithium-ion battery decreases. The combined use of sulfur-containing polyheterocyclic compound A and sulfur-containing monoheterocyclic compound B in lithium-ion electrolyte can combine the advantages of both and further improve the cycle life and thermal safety performance of lithium-ion batteries.

[0037] In some embodiments, the mass ratio of sulfur-containing polyheterocyclic compound A to sulfur-containing monoheterocyclic compound B is (2-6):1. When the relationship between the two further satisfies the above range, since the content of sulfur-containing polyheterocyclic compound A is higher than that of sulfur-containing monoheterocyclic compound B, in the SEI film formed on the surface of the negative electrode, the compound (such as organic sulfonate compound or organic sulfate compound) decomposed by sulfur-containing polyheterocyclic compound A accounts for a higher proportion, and the mechanical elasticity of the SEI film formed is better, which can better restrain the volume expansion of the silicon-containing negative electrode and maintain the stability of the SEI film. Therefore, the cycle capacity retention rate of the lithium-ion battery is better. At the same time, there is a synergistic effect between the appropriate amount of sulfur-containing monoheterocyclic compound B and the sulfur-containing polyheterocyclic compound A, which can make lithium ions have better thermal safety performance;

[0038] In some embodiments, the sulfur-containing polyheterocyclic compound A comprises at least one of the following compounds:

[0039]

[0040] And / or, the sulfur-containing monoheterocyclic compound B includes at least one of the following compounds:

[0041]

[0042] Further selection of the above-mentioned sulfur-containing heterocyclic compounds can make the solid electrolyte film formed on the positive and negative surfaces more stable, further inhibit the volume expansion of the silicon-containing negative electrode and the dissolution of metal ions of the positive electrode material, improve the cycle stability of the silicon-carbon material while inhibiting the high-temperature gas production of the lithium-ion battery, and further improve the thermal safety performance and cycle life of the lithium-ion battery.

[0043] In some embodiments, the mass content of silicon in the silicon-carbon material is 35%-70%, and the mass content of silicon can be, for example, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any point value in the range of any two of the above points. When the mass content of silicon in the silicon-carbon material further meets the above range, it can ensure that the lithium-ion battery has good thermal safety performance and cycle life, so that the negative electrode material has a higher lithium storage capacity, and further improves the energy density of the lithium-ion battery.

[0044] And / or, in the silicon-carbon material, the volume distribution of the silicon-carbon composite material is: Dv10 is 3μm-6μm, Dv50 is 6μm-12μm, and Dv90 is 12μm-25μm. When the volume distribution particle size of the silicon-carbon material is adjusted to further meet the above range, the specific surface area of ​​the material can be further optimized, the effective reaction interface can be increased, and the capacity and cycle life of the battery can be improved.

[0045] And / or, the silicon-carbon material includes a carbon coating layer, which is coated on the surface of the porous carbon substrate and the silicon material; the thickness of the carbon coating layer is 10nm-500nm, and the thickness of the carbon coating layer can be, for example, 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any point value in the range composed of the above two point values. When the thickness of the carbon coating layer is adjusted to further meet the above range, it can be effectively avoided that when the thickness of the carbon coating layer is <10nm, the binding force of the coating layer on the core is weak, and it is easy to crack during the lithium insertion and extraction process, thereby deteriorating the performance of the material; it can also be avoided that when the thickness of the carbon coating layer is >500nm, the distance of lithium ions embedded in the silicon material will be increased, resulting in poor kinetic performance of the material. Therefore, when the thickness of the carbon coating layer is controlled within the above range, the silicon-carbon composite material can be made to have better kinetics and cycle stability.

[0046] In the prior art, roller pressing is usually used to reduce the thickness of the positive and negative electrode sheets and further improve the energy density of lithium-ion batteries. However, roller pressing often causes the compaction density of the positive and negative electrode materials to be too high, and the pores between the materials are relatively reduced, which is not conducive to the infiltration and storage of the electrolyte, and is more likely to cause interface problems related to poor lithium precipitation or lithium insertion. On the other hand, roller pressing will increase the degree of fragmentation of hard particles, such as silicon in silicon-carbon composite materials, to a certain extent, which will lead to greater consumption of electrolyte. Therefore, high compaction density will lead to poor electrolyte storage and infiltration, and the increased electrolyte consumption will further aggravate interface problems such as lithium precipitation.

[0047] First, in the present invention, the sphericity Q of the silicon-carbon material is controlled at a relatively high level (Q satisfies 0.5≤Q≤1), which can inhibit the fragmentation of the silicon-carbon material to a certain extent and is beneficial to reducing the consumption of the electrolyte.

[0048] Secondly, in order to make the lithium-ion battery have a higher energy density and further solve the above-mentioned problems caused by the rolling process, the present invention further proposes on the basis of the above-mentioned original implementation mode: the negative electrode sheet includes a negative electrode current collector, and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector; a recessed area is arranged on the negative electrode active material layer, and the recessed area includes at least one pit; the negative electrode active material layer includes the negative electrode active material; the depth of the pit is recorded as Xμm, X satisfies 5≤X≤45, preferably 5≤X≤30; and / or, the oil absorption value of the silicon-carbon material is recorded as Y mL / 100g, and Y satisfies: 10≤Y≤100, preferably 20≤Y≤50.

[0049] When X and / or Y further satisfy the above range, the lithium-ion battery can have a suitable amount of residual liquid, the negative electrode sheet and the separator have good adhesion and the lithium-ion battery is not easy to deform, which is beneficial to enhance the mass transfer of the positive and negative electrodes, reduce the ion impedance, shorten the transmission distance of lithium ions, improve the wettability of the electrolyte, increase the liquid retention capacity of the battery, slow down the problem of lithium decomposition, and improve the energy density of the battery to a certain extent.

[0050] In some embodiments, the depth X of the pit can be, for example, 5μm, 8μm, 10μm, 12μm, 15μm, 17μm, 20μm, 22μm, 25μm, 27μm, 30μm, 35μm, 40μm, 45μm or any point value in the range of the above two point values. The depth X of the pit further satisfies the above range, which can avoid the limited improvement of the battery dynamics when X<5, and avoid the stress and strain of the electrode material being easily released when X>30, thereby causing the battery to deform during the cycle; it can increase the infiltration of the electrolyte without almost reducing the battery energy density, shorten the distance of lithium ions diffusing to the inside, thereby improving the fast charging ability of the lithium-ion battery, and improving the problems of interface lithium precipitation caused by rolling. In addition, the space formed by the pit can also be used as a storage space for the electrolyte, which is beneficial to improving the cycle life and capacity retention rate of the battery.

[0051] In the present invention, the depth X of the pit is the vertical distance from the surface of the negative electrode active material layer to the bottom of the depression.

[0052] In the present invention, the thickness range of the negative electrode active material layer is 70μm-140μm; illustratively, the thickness of the negative electrode active material layer can be, for example, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or any point value in the range consisting of any two of the above point values.

[0053] In the present invention, the depth X of the pit is less than the thickness of the negative electrode active material layer, and the pit does not penetrate the current collector.

[0054] In some embodiments, the oil absorption value Y of the silicon-carbon material can be, for example, 10 mL / 100 g, 20 mL / 100 g, 30 mL / 100 g, 40 mL / 100 g, 50 mL / 100 g, 60 mL / 100 g, 70 mL / 100 g, 80 mL / 100 g, 90 mL / 100 g, 100 mL / 100 g, or any point value in the range formed by any two of the above point values. The oil absorption value Y further satisfies the above range, which can avoid the problem of poor electrolyte wetting when Y<10 and the problem that the silicon-carbon material is prone to expansion and deformation when Y>1000, further improve the electrolyte wettability and liquid retention of the silicon-carbon material, while maintaining the integrity of its own structure and good adhesion with the binder.

[0055] Exemplarily, the test method of the oil absorption value Y may include the following steps: weigh the mass of a clean beaker and a glass rod as m1, record the total mass after adding 5 g of the composite material as m2, add dioctyl phthalate (DOP) dropwise with a titration bottle, and stir thoroughly, stop adding DOP when a lump is formed, weigh the total weight of the beaker at this time as m3, and the oil absorption value Y = (m3-m2) / (m2-m1)*100.

[0056] In some embodiments, the contour of the pit is at least one of a linear groove, a regular hole shape, or an irregular hole shape.

[0057] In some embodiments, when the contour of the pit is a linear groove, the distance between two adjacent linear grooves is 1mm-3mm, for example, it can be 1mm, 1.5mm, 2mm, 2.5mm, 3mm or any point value in the range of the above two point values. When the distance between two adjacent linear grooves further meets the above range, it can be avoided that due to the large strain of the electrode material inserting and extracting lithium during the cycle of the battery, the adjacent linear grooves are too close to form too much internal space in the pit, which is easy to cause the concentrated release of stress and strain of the negative electrode, thereby causing the battery to deform during the cycle, and prevent the weakening of the adhesion caused by the groove distance being too close, resulting in aggravated deformation of the battery and causing interface problems such as lithium precipitation, which deteriorates the cycle life of the lithium-ion battery; it can also avoid that when the distance between adjacent linear grooves is too far, the improvement of the battery dynamics is limited. Therefore, the distance between two adjacent linear grooves further meets the above range, which can make the negative electrode sheet and the separator have better adhesion and the lithium-ion battery is less likely to deform, further improve the wettability of the electrolyte, increase the battery's liquid retention capacity, and improve the problem of lithium plating at the lithium-ion battery interface, so that the lithium-ion battery has fast charging, high energy density and long cycle life.

[0058] In some embodiments, when the profile of the pit is a regular hole shape or an irregular hole shape, the distance between two adjacent holes is 100μm-300μm, for example, it can be 100μm, 150μm, 200μm, 250μm, 300μm or any point value in the range of the above two point values. Similar to the technical effect produced when the distance between the above two adjacent linear grooves is further 1mm-3mm, when the distance between two adjacent holes of regular hole shape or irregular hole shape further meets the above range, the wettability of the electrolyte can be further improved, the liquid retention of the battery can be increased, and the problem of lithium precipitation at the interface of the lithium-ion battery can be improved, so that the lithium-ion battery has both fast charging, high energy density and long cycle life.

[0059] In some embodiments, Figure 1 As shown, a recessed area 1 is provided on the negative electrode active material layer 3, and a plurality of intervally distributed pits 2 are provided in the recessed area 1, and the pits 2 are regular hole shapes.

[0060] In some embodiments, Figure 2 As shown, a recessed area 1 is provided on the negative electrode active material layer 3 , and a plurality of intervally distributed pits 2 are provided in the recessed area 1 , and the pits 2 are linear grooves.

[0061] The battery also includes a diaphragm; the diaphragm includes a porous substrate, a heat-resistant coating, and a porous bonding layer stacked in sequence; the heat-resistant coating includes inorganic particles, and the Dv50 of the inorganic particles is recorded as Wμm; S and W satisfy: 0.5≤S / W≤20, and the value of S / W can be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any point value in the range composed of the above two point values, preferably 1≤S / W≤15. When S and W further meet the above range, the sulfur-containing heterocyclic compound can passivate part of the dust remaining when the depression area is formed during the film formation of the negative electrode, and the inorganic particles can effectively prevent the contact between the positive and negative electrode dusts by increasing their coverage, thereby jointly improving the self-discharge of the battery, and on the other hand, it can increase the path for the dissolved metal ions to migrate to the negative electrode, thereby extending the thermal safety stability of the lithium-ion battery. In addition, when the Dv50 of the inorganic particles is within the above range, they can have appropriately distributed pores and a reasonable surface area, which can enable the inorganic heat-resistant coating to have a higher liquid absorption capacity. Therefore, the synergistic effect between the inorganic heat-resistant coating and the sulfur-containing heterocyclic compound can enable the prepared lithium-ion battery to have a better ability to inhibit self-discharge and better thermal safety performance.

[0062] Exemplarily, the structure of the diaphragm may be: porous bonding layer + heat-resistant layer + porous substrate + porous bonding layer, porous bonding layer + heat-resistant layer + porous substrate + heat-resistant layer + porous bonding layer. Preferably, the structure of the diaphragm is a porous bonding layer + heat-resistant layer + porous substrate + porous bonding layer structure (the heat-resistant layer is arranged on the side close to the positive electrode sheet).

[0063] In some embodiments, the inorganic particles are selected from at least one of inorganic metal oxides, inorganic metal nitrides, and inorganic metal salts.

[0064] Illustratively, the inorganic metal oxide includes boehmite, aluminum oxide, magnesium oxide, calcium oxide, titanium dioxide, silicon dioxide, and zirconium dioxide.

[0065] Exemplarily, the inorganic metal nitride includes tungsten nitride, silicon carbide, boron nitride, aluminum nitride, titanium nitride and magnesium nitride.

[0066] Illustratively, the inorganic metal salt includes barium sulfate, calcium titanate and barium titanate.

[0067] In some embodiments, the Dv50 (W) of the inorganic particles is 0.2 μm-2 μm, for example, 0.2 μm, 0.4 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm or any point value in the range of the above two point values. When S and W satisfy 0.5≤S / W≤20, the Dv50 of the inorganic particles further satisfies the above range, which can increase the coverage of the inorganic particles on the pole piece, further prevent the contact between the positive and negative electrode dusts, and thus improve the self-discharge of the lithium-ion battery.

[0068] In some embodiments, the bonding force between the separator and the negative electrode sheet is ≥5 N / m. When S and W satisfy 0.5≤S / W≤20, the bonding force between the separator and the negative electrode sheet further satisfies the above range, which can effectively avoid the fact that when the bonding force is <5 N / m, the separator and the negative electrode material are easily peeled off due to repeated expansion and contraction of the negative electrode sheet during the cycle, resulting in a longer transmission distance of lithium ions and worse kinetics, thereby causing interface lithium precipitation or interface adverse phenomena such as black spots and purple spots.

[0069] In some embodiments, the thickness of the porous substrate of the diaphragm is 3 μm-8 μm, for example, it can be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm or any point value in the range consisting of any two of the above point values.

[0070] In some embodiments, the porous substrate may include at least one of polypropylene, polyethylene, polyvinylidene fluoride, polytetrafluoroethylene, and polyimide.

[0071] In some embodiments, the thickness of the heat-resistant coating is 0.5 μm-3 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any point value in the range consisting of any two of the above point values.

[0072] In some embodiments, the thickness of the porous bonding layer is 0.5 μm-3 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any value in the range consisting of any two of the above values.

[0073] In some embodiments, the porous bonding layer may include at least one of polyvinylidene fluoride (PVDF), polymethyl methacrylate, polytetrafluoroethylene-ethylene copolymer, polytetrafluoroethylene, methacrylate, and styrene-butadiene rubber.

[0074] In some embodiments, the carboxylate solvent includes a C1-C10 carboxylate solvent. When Q, E and S satisfy: Further selecting the above carboxylate solvent can be more conducive to reducing the viscosity of the electrolyte and improving the conductivity of the electrolyte, thereby obtaining better kinetic performance.

[0075] Illustratively, the C1-C10 carboxylic acid ester solvent includes one or more of n-propyl propionate, ethyl propionate, methyl propionate, n-butyl propionate, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl butyrate, ethyl butyrate, and propyl butyrate.

[0076] In some embodiments, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a lithium cobalt oxide-based layered oxide material. Since the lithium cobalt oxide-based layered oxide material has a higher capacity and a higher voltage platform, and can obtain a higher compaction density, the use of the lithium cobalt oxide-based layered oxide in the lithium ion battery is conducive to the lithium ion battery to obtain a higher energy density.

[0077] In some embodiments, the lithium cobalt oxide-based layered oxide material includes a carbon coating layer.

[0078] In some embodiments, the lithium cobalt oxide-based layered oxide material includes a doping element. Exemplarily, the doping element includes but is not limited to at least one of Na, K, Cs, Mg, Ca, Ba, Al, Ti, Ta, Ni, Fe, Mn, W, Sc, Tc, Zr, Ta, Sr, and Y.

[0079] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90wt%-99.4wt% of positive electrode active material, 0.3wt%-5wt% of conductive agent, and 0.3wt%-5wt% of binder.

[0080] Exemplarily, the mass percentage of the positive electrode active material in the positive electrode active material layer can be, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99.4wt% or any point value in the range composed of any two of the above point values.

[0081] Illustratively, the mass percentage of the conductive agent in the positive electrode active material layer can be, for example, 0.3wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.

[0082] Illustratively, the mass percentage of the binder in the positive electrode active material layer can be, for example, 0.3wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.

[0083] In some embodiments, the mass percentage of each component in the negative electrode active material layer is: 90wt%-99.4wt% of negative electrode active material, 0.2wt%-5wt% of conductive agent, and 0.4wt%-5wt% of binder.

[0084] Exemplarily, the mass percentage of the negative electrode active material in the negative electrode active material layer can be, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99.4wt% or any point value in the range composed of any two of the above point values.

[0085] Illustratively, the mass percentage of the conductive agent in the negative electrode active material layer can be, for example, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.

[0086] Illustratively, the mass percentage of the binder in the negative electrode active material layer can be, for example, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.

[0087] In some embodiments, the conductive agent includes, but is not limited to, one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0088] In some embodiments, the binder includes but is not limited to one or more of styrene-butadiene rubber latex, polytetrafluoroethylene latex, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, and carboxylated chitosan.

[0089] In some embodiments, the lithium ion electrolyte further comprises a lithium salt, which may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium difluorophosphate (LiPO 2 F 2 ), lithium hexafluoroantimonate (LiSbF 6 ) lithium hexafluoroarsenate (LiAsF 6), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate (LiBF 4 ), lithium bis(difluorophosphoryloxy)difluoroborate, lithium tetrakis(difluorophosphoryloxy)borate or one or more thereof. Based on the total mass of the electrolyte, the mass proportion of the lithium salt is 12.5%-25%, for example, it can be 12.5%, 15%, 18%, 20%, 22%, 24%, 25% or any point value in the range composed of any two of the above points. Adding a lithium salt that meets the above range to the electrolyte can improve the ionic conductivity of the electrolyte, improve the charge and discharge efficiency of the battery, and improve the fast charging performance of the battery.

[0090] In some embodiments, the lithium ion electrolyte further includes other additives, and the other additives can be selected from one or more additives commonly used in the art to further improve the cycle performance or high and low temperature performance of the battery. Exemplarily, the additives include but are not limited to vinylene carbonate (VC), fluoroethylene carbonate (FEC), succinonitrile (SN), adiponitrile (AND), glutaronitrile (GN), hexane trinitrile (HTCN), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), tetravinylsilane (TVS), tris (trimethylsilyl) borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), pentafluoroethoxy cyclotriphosphazene (PFPN) One or more. Based on the total mass of the electrolyte, the mass proportion of the other additives is 8%-20%, for example, it can be 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of the above two point values.

[0091] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0092] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0093] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0094] Example 1-1

[0095] (1) Preparation of negative electrode sheet:

[0096] The negative electrode active material (composed of 90wt% artificial graphite + 10wt% of the silicon-carbon composite material), styrene-butadiene rubber (SBR), lithium polyacrylate, conductive carbon black (SP) and carbon nanotubes (CNTs) are mixed uniformly according to a mass ratio of 96.5:1.5:0.5:1.0:0.5, and then an appropriate amount of deionized water is added step by step to obtain a negative electrode slurry under the action of a vacuum mixer. The sphericity Q of the silicon-carbon composite material used is 0.9, and the oil absorption value is 40mL / 100g. The negative electrode active slurry is evenly coated on both surfaces of the copper foil by a coating machine; the coated copper foil is dried at room temperature until the surface is dry, and then transferred to an oven at 80°C for drying for 10 hours, and then rolled, laser wired, and cut to obtain a negative electrode sheet. Among them, the pit depth formed by the negative electrode wire is 20μm, and the distance between the grooves between the lines is 2mm.

[0097] (2) Preparation of positive electrode sheet:

[0098] Carbon-coated lithium cobalt oxide (LiCoO 2 @C) materials, polyvinylidene fluoride (PVDF), conductive carbon black (SP) and carbon nanotubes (CNTs) are dry mixed in a mass ratio of 96:2.0:1.5:0.5. Then, under the action of a vacuum mixer, an appropriate amount of N-methylpyrrolidone (NMP) is gradually added to mix into a uniform slurry. Subsequently, a coating machine is used to evenly coat the positive electrode active slurry on both surfaces of the aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the required positive electrode sheet.

[0099] (3) Preparation of diaphragm:

[0100] A 2 μm thick aluminum oxide layer (composed of 92 wt% aluminum oxide, 4 wt% methacrylic acid, and 4 wt% sodium polymethylcellulose) was coated on the first surface of a 5 μm thick porous polypropylene substrate, and the average particle size of the aluminum oxide particles was 0.5 μm. Subsequently, a 1 μm thick bonding layer was coated on the second surface of the polypropylene substrate opposite to the first surface and on the surface of the aluminum oxide layer, and the material of the bonding layer was PVDF.

[0101] (4) Preparation of electrolyte:

[0102] In a glove box filled with argon (H 2 O<0.1ppm, O 2 <0.1ppm), ethylene carbonate (EC), propylene carbonate (PC), ethyl butyrate (EB, carboxylate solvent), and n-propyl acetate (PA, carboxylate solvent) were mixed in an appropriate mass ratio. Then, 12wt% of LiPF based on the total mass of the electrolyte was quickly added.6 and 5wt% LiTFSI, and after dissolving, 10wt% FEC, 1.0wt% 1,3,6-hexanetrinitrile (HTCN), 0.5wt% sulfur-containing monoheterocyclic compound B of formula XVI and 1.5wt% sulfur-containing polyheterocyclic compound A of formula I are added. After stirring evenly, the desired electrolyte is obtained after passing the tests of moisture, free acid, chromaticity, etc. In the electrolyte, the total mass ratio of ethyl butyrate and n-propyl acetate is 45%, and the mass ratio of ethylene carbonate and propylene carbonate is 1:1 (the total mass ratio of the two changes with the mass ratio of the carboxylic acid ester solvent).

[0103] (5) Preparation of lithium-ion batteries:

[0104] The negative electrode sheet, separator, and positive electrode sheet are stacked in a certain way so that the separator completely separates the positive and negative electrodes, and the negative electrode paste completely covers the positive electrode paste, and then a roll core with a certain thickness and width is made by winding. Subsequently, an aluminum-plastic film is used for packaging and the electrolyte prepared in the above steps is injected. After vacuum packaging, aging, formation, shaping, sorting and other processes, a soft-pack lithium-ion battery with certain specifications is obtained. The prepared lithium-ion voltage test window is 3.0V-4.53V.

[0105] (6) Test methods for performance parameters:

[0106] (i) K value test method: Measure the open circuit potential of the sorted lithium-ion battery to obtain V1, let it stand for 24 hours, and measure the open circuit potential of the battery again to obtain V2. The difference between V1 and V2 is divided by the standing time to obtain the K value of the battery.

[0107] (ii) Hot box test: First, the lithium-ion battery is fully charged at a constant current and voltage of 0.5C, and the fully charged battery is placed in a constant temperature box at 20±5℃. Then, the temperature is raised to the target temperature at a rate of 5℃ / min and kept at a constant temperature for 30 minutes. If the battery does not catch fire or explode within 30 minutes, it means that the battery has passed the hot box test.

[0108] (iii) Cyclic performance test: In a constant temperature box at 25°C, the battery was charged to the upper limit voltage at an initial rate of 4C, and then charged at a constant voltage until the current dropped to 0.05C. After the charging process, it was left to stand for 10 minutes, and then discharged to 3.0V at a rate of 0.7C. One charge and discharge process is one cycle. The cycle life of the battery is characterized by the capacity of the battery dropping to 80% of the initial capacity.

[0109] (iv) Test method for adhesion between separator and negative electrode

[0110] The batteries obtained in the above embodiments and comparative examples were placed in an environment of (25±2)°C and left to stand for 2-3h. The batteries were charged at a constant current of 0.7C with a cut-off current of 0.05C. When the battery terminal voltage reached the charging limit voltage, constant voltage charging was performed until the charging current ≤ the cut-off current. Charging was stopped and left for 5min. The fully charged batteries were dissected. The national standard GB / T2790-1995, i.e., the 180° peel test standard was used to test the adhesion between the isolation film and the positive electrode sheet or the negative electrode sheet. The isolation film and the negative electrode sheet were cut into 15mm×54.2mm strips. The adhesion between the isolation film and the negative electrode sheet was tested according to the 180° peel test standard.

[0111] (v) Testing method of particle size of silicon-carbon composite material: Particle sizes Dv10, Dv50 and Dv90 can be measured by laser particle size testing method. For example, the Malvern particle size tester is used for measurement. The testing steps are as follows: the composite material is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in the Malvern particle size tester for testing.

[0112] (vi) Lithium-ion battery storage test at 60°C:

[0113] The lithium-ion battery is fully charged and placed in a 60°C thermostat, and the thickness of the battery is measured every 3 days until the thickness of the battery expands by more than 10% of the initial thickness. The recorded number of days (D) is the 60°C storage life of the lithium-ion battery.

[0114] The examples 1 to 3, and comparative examples 1 to 4 were carried out with reference to the examples 1 to 1, and the main differences are shown in Table 1. In the example 1 group, the mass proportion of the carboxylic acid ester solvent in the electrolyte was changed; in the example 2 group, the mass proportion of the sulfur-containing heterocyclic compound in the electrolyte was changed; and in the example 3 group, the sphericity of the silicon-carbon material was changed. In comparative example 1, the mass proportion of the carboxylic acid ester solvent in the electrolyte was too small; in comparative example 2, the mass proportion of the sulfur-containing heterocyclic compound was too small; in comparative example 3, the mass proportion of the sulfur-containing heterocyclic compound was too large; and in comparative example 4, no sulfur-containing heterocyclic compound was added.

[0115] Table 1

[0116]

[0117]

[0118] Note: “ / ” indicates that the corresponding parameter is not tested.

[0119] As can be seen from Table 1, the present invention adjusts the sphericity Q of the silicon-carbon material within the range of 0.5-1, and at the same time adjusts the mass proportion E of the carboxylic acid ester solvent and the mass proportion S of the sulfur-containing heterocyclic compound in the electrolyte to satisfy 10≤E / S≤100, so that the lithium-ion battery can have good kinetic performance, high energy density, good cycle stability and good thermal safety performance.

[0120] Example 4 was carried out with reference to Example 1-1, and the main differences are shown in Table 2. In Example 4, the mass proportion of the sulfur-containing heterocyclic compound in the electrolyte was kept unchanged, and the type of the sulfur-containing heterocyclic compound or the ratio between the sulfur-containing polyheterocyclic compound A and the sulfur-containing monoheterocyclic compound B was changed.

[0121] Table 2

[0122]

[0123] As can be seen from Table 2, the present invention can further improve the cycle life and thermal safety performance of lithium-ion batteries by adjusting the type and proportion of sulfur-containing heterocyclic compounds added to the electrolyte.

[0124] The examples 5 and 6 were carried out with reference to the examples 1-1, and the main differences are shown in Table 3. In the example 5, the mass content of silicon in the silicon-carbon material was changed; and in the example 6, the thickness of the carbon coating layer was changed.

[0125] Table 3

[0126]

[0127] As can be seen from Table 3, the present invention can ensure that the lithium-ion battery has good thermal safety performance, cycle life and fast charging performance by adjusting the mass content of silicon in the silicon-carbon material, while making the negative electrode material have a higher lithium storage capacity, thereby further improving the energy density of the lithium-ion battery; by adjusting the thickness of the carbon coating layer, the silicon-carbon composite material can have better dynamics and cycle stability.

[0128] The examples 7-8 were carried out with reference to the examples 1-1, and the main differences are shown in Table 4. In the example 7, the depth of the pits and / or the oil absorption value of the silicon-carbon material were changed; and in the example 8, the distance between adjacent linear grooves was changed.

[0129] Table 4

[0130]

[0131] As can be seen from Table 4, the present invention can improve the wettability of the electrolyte, increase the liquid retention of the battery, alleviate the problem of lithium desorption, and enhance the fast charging performance of the lithium-ion battery by adjusting the depth X of the pit and the oil absorption value Y of the silicon-carbon material; by adjusting the distance between adjacent linear grooves, the negative electrode sheet and the diaphragm can have better adhesion and the lithium-ion battery is less likely to deform, further improving the wettability of the electrolyte, increasing the liquid retention of the battery, improving the problem of lithium desorption at the interface of the lithium-ion battery, improving the fast charging performance of the lithium-ion battery, and extending the cycle life.

[0132] The examples 9 and 10 were carried out with reference to the examples 1-1, and the main differences are shown in Table 5. In the example 9, the Dv50 of the inorganic particles in the heat-resistant coating was changed; and in the example 10, the mass proportion of the sulfur-containing heterocyclic compound in the electrolyte was changed.

[0133] Table 5

[0134]

[0135] It can be seen from Table 5 that the present invention adjusts the Dv50 (W) of the inorganic particles in the heat-resistant coating and the mass proportion (S) of the sulfur-containing heterocyclic compound in the electrolyte so that S and W satisfy 0.5≤S / W≤20. The synergistic effect between the inorganic heat-resistant coating and the sulfur-containing heterocyclic compound can enable the prepared lithium-ion battery to have better ability to inhibit self-discharge and better thermal safety performance.

[0136] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the sphericity of the silicon-carbon material is denoted as Q, and the sphericity Q is 0.5-1; The electrolyte includes a carboxylate solvent; based on the total mass of the electrolyte, the mass proportion of the carboxylate solvent is recorded as E%; The electrolyte includes a sulfur-containing heterocyclic compound; the mass proportion of the sulfur-containing heterocyclic compound is recorded as S% based on the total mass of the electrolyte; E and S satisfy: 10≤E / S≤100.

2. The lithium ion secondary battery according to claim 1, characterized in that: E and S satisfy: 15≤E / S≤80; And / or, the mass proportion E of the carboxylic acid ester solvent is 30%-60%; And / or, the mass percentage S of the sulfur-containing heterocyclic compound is 0.5%-5%.

3. The lithium ion secondary battery according to claim 1, characterized in that: The sulfur-containing heterocyclic compound includes a sulfur-containing polyheterocyclic compound A, and / or a sulfur-containing monoheterocyclic compound B; Preferably, the sulfur-containing heterocyclic compound comprises: a sulfur-containing polyheterocyclic compound A and a sulfur-containing monoheterocyclic compound B; Preferably, the mass ratio of the sulfur-containing polyheterocyclic compound A to the sulfur-containing monoheterocyclic compound B is (2-6):

1.

4. The lithium ion secondary battery according to claim 3, characterized in that: The sulfur-containing polyheterocyclic compound A comprises at least one of the following compounds: And / or, the sulfur-containing monoheterocyclic compound B includes at least one of the following compounds:

5. The lithium ion secondary battery according to claim 1, characterized in that: In the silicon-carbon material, the mass content of silicon element is 35%-70%; Preferably, the volume distribution of the silicon-carbon material is: Dv10 is 3 μm-6 μm, Dv50 is 6 μm-12 μm, and Dv90 is 12 μm-25 μm; Preferably, the silicon-carbon material includes a carbon coating layer, and the thickness of the carbon coating layer is 10 nm-500 nm.

6. The lithium ion secondary battery according to claim 1, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; a recessed area is disposed on the negative electrode active material layer, and the recessed area comprises at least one pit; the negative electrode active material layer comprises the negative electrode active material; the depth of the pit is recorded as X μm, and X satisfies: 5≤X≤45, preferably 5≤X≤30; And / or, the oil absorption value of the silicon-carbon material is recorded as Y mL / 100g, where Y satisfies: 10≤Y≤100, preferably 20≤Y≤50.

7. The lithium ion secondary battery according to claim 6, characterized in that: The outline of the pit is a linear groove, a regular hole shape or an irregular hole shape; Preferably, when the profile of the pit is a linear groove, the distance between two adjacent linear grooves is 1 mm-3 mm; Preferably, when the contour of the pit is a regular hole shape or an irregular hole shape, the distance between two adjacent holes is 100 μm-300 μm.

8. The lithium ion secondary battery according to claim 6, characterized in that: The battery further comprises a separator; the separator comprises a porous substrate, a heat-resistant coating, and a porous bonding layer stacked in sequence; The heat-resistant coating comprises inorganic particles, and the Dv50 of the inorganic particles is recorded as W μm; S and W satisfy: 0.5≤S / W≤20, preferably 1≤S / W≤15; Preferably, the Dv50 of the inorganic particles is 0.2 μm-2 μm.

9. The lithium ion secondary battery according to claim 8, characterized in that: The bonding force between the separator and the negative electrode sheet is ≥5N / m; Preferably, the thickness of the porous substrate of the separator is 3 μm-8 μm; and / or the thickness of the heat-resistant coating is 0.5 μm-3 μm; and / or the thickness of the porous bonding layer is 0.5 μm-3 μm.

10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: The carboxylate solvent includes a C1-C10 carboxylate solvent; preferably, the C1-C10 carboxylate solvent includes one or more of n-propyl propionate, ethyl propionate, methyl propionate, n-butyl propionate, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl butyrate, ethyl butyrate, and propyl butyrate; The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a lithium cobalt oxide-based layered oxide material.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode and preparation method thereof and lithium ion battery

    CN110085806A

  • Separator for lithium secondary battery, and lithium secondary battery comprising same

    CN113261153A

  • Electrolyte and lithium ion battery containing same

    CN117133979A

  • Silicon-carbon composite negative electrode material, preparation method and application

    CN118173769A

  • Etchant compositions and methods of manufacturing semiconductor device using the same

    KR1020250052943A

Cited By

  • Secondary battery and electronic device

    WO2026156807A1

  • Lithium-ion secondary battery

    WO2026171080A1